PEMANFAATAN MEDIA CANVA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS III SD NEGERI 1 KUBU BANGLI - Asmara, Kadek Dwi Gina; Linggih, I Nyoman; Suciartini, Ni Nyoman Ayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of information and communication technology has encouraged the integration of digital learning media to improve the quality of teaching and learning processes in elementary schools. One of the digital platforms that can be utilized is Canva, a graphic design application that enables teachers to present learning materials in a visual, interactive, and engaging manner. This study aimed to describe the implementation of Canva in Pancasila Education learning, students’ responses to its use, and its impact on third-grade students at SD Negeri 1 Kubu. The research employed a descriptive qualitative approach involving a third-grade teacher, third-grade students, and the school principal as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that the implementation of Canva was carried out through three stages: planning, implementation, and evaluation. Canva was utilized to present learning materials through visual presentations, images, animations, and videos that were appropriate to the characteristics of elementary school students. The use of Canva received positive responses from students, as reflected in increased attention, participation, discipline, and understanding of the learning materials. Therefore, Canva can serve as an effective digital learning medium to support Pancasila Education learning in elementary schools.